Generation and detection of [C59N]+ by laser desorption/ionisation high-field Fourier transform ion cyclotron resonance mass spectrometry - Feng, X.; Clipston, Nigel; Brown, T.; Cooper, H.; Reuther, Uwe; Hirsch, Andreas; Derrick, P. J.; Drewello, Thomas (Rapid Communications in Mass Spectrometry, 2000)
Important parameters to consider when developing a liquid chromatography/mass spectrometry (LC/MS) method are buffer type and concentration, and column geometry. In the work presented here the choice of buffer for the analysis of basic compounds using a polar embedded phase (HyPURITY(TM) ADVANCE) is illustrated for the analysis of tricyclic antidepressants. Method transfer from a 4.6 mm i.d. column to a 2.1 mm i.d. column is demonstrated for the analysis of triazines and anabolic steroids and their metabolites, with no change in selectivity and with added speed of analysis. Analysis of eight β-blockers is achieved in 65 seconds by using a short 30 x 4.6 mm C18 column. (C) 2000 John Wiley and Sons, Ltd.